IPTEK bagi Masyarakat Perbatasan Entikong dalam Pengolahan Kerajinan Bambu - Tavita, Gusti Eva; Warsidah, Warsidah; Aritonang, Anthoni B.; Ashari, Asri Mulya (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
Entikong is one of Indonesia's land border areas with Sarawak Malaysia, which is the gateway for economic and business activities. Despite being the front porch of a country, the fact is that the border areas of the State are very conditioned with lag. Limited access to public service resources and the inadequate community ability in processing natural resources including agriculture and plantations are the dominant factors influencing the lag of a border area. Bamboo is one of the abundant forest products in Entikong. The use of bamboo in the community is still limited to its use as building materials (scaffolding) and as a protective fence for plants in the gardens of the citizens. Bamboo Rope (Gigantochloa hasskarliana Kurz) species of bamboo found in the Entikong region, where elsewhere it generally makes it as a household handicraft material, but has not been used effectively in the entikong region. Community service activities aim to improve the skills of the Entikong community in processing bamboo plants as handicrafts of household goods of economic value so that it can be an additional source of income for the people on the border ===== Entikong adalah wilayah perbatasan darat Indonesia dengan Sarawak Malaysia, yang menjadi gerbang kegiatan ekonomi dan perniagaan. Meskipun menjadi beranda depan dari suatu negara, kenyataannya bahwa wilayah batas negara sangat sarat dengan ketertinggalan. Keterbatasan mengakses sumber-sumber pelayanan masyarakat dan kemampuan masyarakat yang tidak memadai dalam mengolah sumber daya alam termasuk pertanian dan perkebunan merupakan faktor yang dominan memengaruhi ketertinggalan sebuah wilayah perbatasan. Bambu adalah salah satu hasil hutan yang kelimpahannya besar di daerah Entikong. Pemanfaatan bambu dalam masyarakat masih terbatas pada penggunaannya sebagai bahan bangunan (perancah) dan sebagai pagar pelindung tanaman di kebun-kebun warga. Bambu tali (Gigantochloa hasskarliana Kurz.) adalah salah satu spesies bambu yang terdapat di wilayah Entikong. Di tempat lain umumnya menjadikannya sebagai bahan kerajinan rumah tangga, tetapi belum dimanfaatkan secara efektif di wilayah Entikong. Kegiatan Pengabdian kepada Masyarakat bertujuan untuk meningkatkan keterampilan warga masyarakat Entikong dalam mengolah tanaman bambu sebagai kerajinan alat-alat rumah tangga yang bernilai ekonomis sehingga dapat menjadi sumber penghasilan tambahan masyarakat di perbatasan tersebut.